DIGITALISASI METODE KONSTRUKSI PADA PROYEK HIGH-RISE BUILDING - Silitonga, Daniel Maranatha; Hendrawan, Stefanus Yobel; Jin, Oei Fuk (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
The construction of high-rise buildings is one of the tasks with high levels of risk and complex coordination. Technological innovations such as the internet of things (IoT), 3D printing, virtual reality (VR), artificial intelligence (AI), and building information modeling (BIM) have become solutions in facing the existing risks and challenges. The systematic literature review (SLR) method is used to analyze the development of digital transformation in high-rise building construction projects, so that the extent to which technology can help improve project efficiency, productivity, and quality can be understood. The stages of this SLR method are carried out through literature collection, identification process, and analysis of relevant articles on the discussion topic. Out of the 48 selected literature studies, it is shown that current construction digitalization involves the use of technology 4.0, construction robots, and automatic construction methods. All three have great potential for effective and efficient project management performance, as well as reducing occupational safety risks. However, the implementation of digital technology still faces various challenges, especially in terms of infrastructure provision and skilled human resources. Abstrak Proyek konstruksi high-rise building merupakan salah satu pekerjaan dengan tingkat risiko yang tinggi serta koordinasi yang kompleks. Inovasi teknologi seperti internet of things (IoT), 3D printing, virtual reality (VR), artificial intelligence (AI) hingga building information modeling (BIM) telah menjadi solusi dalam menghadapi risiko serta tantangan yang ada. Metode systematic literature review (SLR) digunakan dalam menganalisis perkembangan transformasi digital pada proyek konstruksi high rise building, sehingga dapat diketahui sejauh mana peran teknologi dapat membantu meningkatkan efisiensi, produktivitas, dan kualitas proyek. Tahapan metode SLR ini dilakukan melalui pengumpulan literatur, proses identifikasi, hingga analisis artikel-artikel yang relevan terhadap topik pembahasan. Dari 48 studi literatur yang dipilih, menunjukkan bahwa digitalisasi konstruksi saat ini berupa penggunaan teknologi 4.0, robot konstruksi, serta metode konstruksi otomatis, ketiga hal tersebut memiliki potensi yang besar terhadap kinerja manajemen proyek yang efektif dan efisien, serta dapat mengurangi risiko keselamatan kerja. Meskipun demikian, implementasi teknologi digital masih menghadapi berbagai tantangan khususnya dalam hal penyediaan infrastruktur serta tenaga manusia yang terampil.